Towards a Political Theology of World Politics: Vassilios Paipais (ed.), Theology and World Politics. Metaphysics, Genealogies, Political Theologies, Cham: Palgrave Macmillan, 2020, pp. 349 - Makris, Spiros (Dia-noesis: A Journal of Philosophy, 2024)
Vassilios Paipais’ edited collective volume entitled Theology and World Politics. Metaphysics, Genealogies, Political Theologies constitutes one of the recent most illuminated and specialized books on the topic of political theology with regard to world politics. The book is divided into three individual parts that bring to the fore the basic aspects of the political theology of the International in our days: that is to say, Metaphysics, Genealogies, and Political Theologies.The preeminent contributors of the collective volume compose a disciplinarily diverse, however absolutely solid, group of contemporary academics and experts of political theology, who approach world politics from different theoretical angles, exploiting the radical conceptual edifice of political theology, in particular the rich and increasingly interconnected intellectual toolkits of philosophy -not only so-called Continental Philosophy (Kahn, 2016)- and theology -not only Christian Theology.